PENGARUH PENGETAHUAN PAJAK, ETIKA, DAN PERAN DOSEN TERHADAP PERSEPSI MAHASISWA TENTANG PRAKTIK PENGGELAPAN PAJAK - Kinar Yosi Sawitri; Andri Waskita Aji; Anita Primastiwi (AKURAT | Jurnal Ilmiah Akuntansi FE UNIBBA, 2022)
Basically, the emergence of perceptions about a material topic for each individual is different. Many factors can influence this perception, including the knowledge possessed, ethics, and how the role given by other people specifically in this study will be analyzed is the role of a lecturer. The topic of the material is about the practice of tax evasion. The objects sampled in this study were 100 students of the Faculty of Economics, Universitas Sarjanawiyata Tamansiswa Yogyakarta. Based on the results of SPSS data processing and analysis, it can be concluded that tax knowledge partially does not have a significant positive effect on student perceptions. While ethics and the role of lecturers partially have a significant positive effect on students' perceptions of tax evasion practices. The results of the R Square test resulted in a number of 0.89 (89%) meaning, the ability of the variable knowledge of tax, ethics and the role of lecturers in explaining student perceptions of tax evasion practices was strong, which was 89%, while the remaining 11% could be explained by other variables outside research